Caesarean section rates and indications in the Democratic Republic of the Congo: The case of Mbandaka City - Mundembe, Patrick Bongbanga; Mbungu, Roger Mwimba; Tshimungu, Félicien Kandolo; Kangite, Jules Moti; Likulu, Jean Claude Efoloko; Bikoko, Guillin Boboko; Mawunu, Monizi; Koto-Te-Nyiwa Ngbolua, Jean-Paul (Orapuh Journal, 2025)
Introduction Caesarean section (CS) is a medically appropriate intervention for managing complications during childbirth. However, the increasing number of both scheduled and emergency CS procedures has led to concerns about the potential overuse of this technique. This trend has contributed to growing mistrust within the community, particularly in areas where CS is frequently performed. It is essential to examine the rates and indications for caesarean sections to understand the factors contributing to this increase and to address the concerns surrounding its use. Purpose The purpose of this study was to evaluate the rate and primary indications for caesarean sections performed in Mbandaka, focusing on the period between 2022 and 2023. The study aimed to identify the main factors influencing the decision to perform a caesarean section and to provide evidence for improving maternal health practices in the region. Methods A quantitative, descriptive, and cross-sectional design was used in this study. The research was conducted across the three health zones of Mbandaka: Bolenge, Mbandaka, and Wangata. A probabilistic, stratified, proportional, and multiphasic sampling technique was employed to select 552 respondents, distributed proportionally across 10 health facilities in the three zones. The data collected included the number of caesarean sections performed, their scheduling status, and the indications for each procedure. Results The study found a caesarean section rate of 32% for the period from 2022 to 2023, with 37.3% being scheduled and 62.7% emergency procedures. The main indications were fetal distress (38.4%) and macrosomia (28.3%). Several factors significantly increased the likelihood of caesarean delivery, including macrosomia (16.4 times more likely), a scarred uterus (28.91 times), a shrunken pelvis (27.8 times), fetal distress (16.8 times), transverse presentation (32.1 times), and twin pregnancies (144.6 times). These findings highlight the substantial impact of medical conditions on caesarean delivery decisions, reflecting the high reliance on caesarean sections for managing childbirth complications in Mbandaka. Conclusion The high CS rate in Mbandaka underscores the importance of improving maternal health practices and prenatal care to minimize risk factors that lead to the need for caesarean delivery. Educational programs aimed at increasing community awareness of the benefits and risks associated with CS are essential for reducing mistrust and ensuring informed decision-making. Furthermore, improving access to timely medical interventions and promoting strategies for preventing complications such as fetal distress and macrosomia could reduce the need for emergency caesarean sections and enhance overall maternal and child health.